Wet Gas Flow Performance Analysis in Undulating Pipe - SURADILAGA (NIM 12203039), RANGGA
Multiphase flow phenomenon can occur in several hydrocarbon production system. One of these phenomenon occurs in transportaion of wet gas through pipeline and cause several problem in fluid transmition operation. Pressure an temperature changes can resluts in formation of liquid holdup. Liquid holdup is the accumulation of liquid due to the difference in velocity (slip) between the phases existing and the influence of gravity. Pipeline profile representing the inclination in every point of a pipeline; this profile affect the liquid holdup, the flow regime, and thereby the pressure loss. Liquid holdup that formed can increase the pressure drop and reduce pipe efficiency. To overcome those problems, sufficient simulation studies to analyze wet gas behaviour in undulating pipe should be conducted. The simulation results can be used by field engineer to determine the optimum condition for wet gas transmition and to determine wich segment of the pipe that need further handling.